Positive Contribution of Creativity and Independence to Student Learning Outcomes in Digital Communication Simulation - Suryani, Irma; Maksum, Hasan (Journal of Education Reseach and Evaluation, 2020)
This study aims to measure and analyze the contribution of creativity and independence to student learning outcomes in the tenth-grade digital communication simulation subject in the Department of Tourism. This type of research is quantitative with a correlational approach. The population of this research is 287 people. Sampling in this study was carried out using a proportional random sampling technique. Samples were taken randomly, as much as 20% of the total population. So that 57 respondents were obtained as a sample. The data collection instrument used a questionnaire using a Likert scale. The data analysis technique in this study used simple regression analysis and multiple regression. The results showed the regression equation, Y = 20,211+0,274X1+0,292X2. The data analysis result also showed that learning creativity contributed to learning outcomes by 32.4%. Learning independence contributed to learning outcomes by 42.7%, and learning creativity and learning independence contributed to learning outcomes by 49.5%. Based on these results, learning creativity and learning independence contribute to student learning outcomes in the tenth-grade digital communication simulation subject of the Tourism Department.